Gnesioi filoi: George Syncellus and Theophanes the Confessor – Addenda - Kompa, Andrzej (Studia Ceranea, 2022)
The paper provides the addenda to A. Kompa, Gnesioi filoi: the search for George Syncellus’ and Theophanes the Confessor’s own words, and the authorship of their oeuvre, Studia Ceranea 5, 2015, p. 155–230. All the expressions crucial to the stylistic and stylometric argument on the authorship of the Chronography of Theophanes have been updated after 7 years and verified in the expanded TLG database. The updated results are presented below. The conclusions confirm the previous opinions on the individual, singular authorship of the chronicle of Theophanes with differences in style from the first part of the universal history, written by George Syncellus. At the same time, both works should be treated as a single project, and the prooimion to Theophanes’ part as a sound base faor the reconstruction of the writing process. The clauses ὡς προέφην, καθὼς καὶ προέφην, ὡς προέφημεν, and καθὼς προέφημεν are specific to the Chronography of Theophanes in their frequency and diversity, but they seem to be known and used by the circles from which Theophanes acquired his literary skills.